Asian Economic Community with Selected Macroeconomic Variables for Exports Sustainability - Romprasert, Suppanunta (International Journal of Economics and Financial Issues, 2013)
<!–[if gte mso 9]> <![endif]–> ASEAN Economic Community is active in Blueprint on 20 November 2007. One activity is exports with free movement of goods and services, investment, skill labors and free flow of capital. It implies that number of outputs will be crated relating to use more workers. Once country produces many outputs, it will affect to change in GDP. Purpose is to search which selected macroeconomic variable including AEC are mostly affected to Thailand exports and to check relationship between GDP and unemployment. Two models are used. One is to identify variables on exports’ movements. Other is to explain relationship between GDP and unemployment. Outcome shows significance AEC has positive effect on exports. Furthermore, raising GDP has an effect on unemployment rate according to Okun’s law in economic theory. It is important for consumers, investors, foreigners and government to understand how effective factors improve for Thailand exports to make benefit in long run. Keywords: Asian Economic Community; exports; GDP; unemployment rate; macroeconomics JEL Classifications: E00; E20; F62 <!–[if gte mso 9]> Normal 0 false false false <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:à¸•à¸²à¸£à¸²à¸‡à¸›à¸à¸•à¸´; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>